Case report: Allogeneic feline umbilical cord-derived mesenchymal stem cell transplantation for feline oral squamous cell carcinoma - Park, Mi-Kyung; Song, Kun-Ho (Frontiers in Veterinary Science, 2024)
A 5-year-old neutered female Korean domestic shorthair cat diagnosed with oral squamous cell carcinoma (SCC) presented to the hospital with severe oral purulent discharge, anorexia, and lethargy. Owing to extensive lesions, surgical excision and radiation therapy were not feasible. Instead, prior to metronomic therapy with toceranib, the patient received an intravenous injection of feline umbilical cord-derived mesenchymal stem cells (fUC-MSCs) (1×10 6 cells/10 mL of saline) to reduce inflammation. No acute side effects (such as fever, increased respiratory rate, diarrhea, and vomiting) were observed following stem cell therapy. For 6 days, purulent discharge, bleeding, swelling, a bad odor, and crust exfoliation in the tumor area on the face were dramatically reduced. However, the patient exhibited difficulty in voluntarily receiving foods, and weight loss persisted. Starting from the 7th day, purulent discharge, bleeding, and odor at the SCC area worsened again. Toceranib, low-dose NSAIDs (meloxicam, every other day), antibiotics (cefazoline), and gabapentin were administered; however, they were not effective in reducing the pus, bleeding, foul odor, and crust exfoliation at the SCC area. Symptoms of pain, weakness, and weight loss progressed, leading to the choice of euthanasia with the owner's consent approximately one month later. This case report reveals that allogeneic fUC-MSCs have a slight short-term effect on purulent discharge, bleeding, odor, and crust exfoliation and may be additional therapy for feline oral SCC.